Analisis Pengaruh Lingkungan Kerja, Work Engagement dan Work Life Balance terhadap Motivasi Kerja Tenaga Pengajar: Analysis of the Influence of Work Environment, Work Engagement, and Work-Life Balance on Work Motivation of Teaching Staff - Sari, Selly Nurlela; Safitri, Ani; Mahrizal, Mahrizal; Wulandari, Ayu Ratna; Sinaga, Victor Lamboy; Mulyani, Nani (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This study evaluated the influence of work environment, engagement, and work-life balance on employee motivation. This study used a quantitative approach and involved 150 respondents. According to multiple linear regression data analysis, work environment, work engagement, and work-life balance affect teacher work motivation. Among the three, work engagement has the most significant impact on motivation to work. Work engagement plays a vital role in teachers' emotional and cognitive involvement in their work, making them feel more connected and enthusiastic about completing the tasks given. Teachers with high levels of work engagement tend to be more proactive, responsible, and satisfied with their work. This creates higher work enthusiasm and improves the quality of teaching. In addition, a conducive work environment, both physically and non-physically, also increases teacher motivation. A supportive workplace, with adequate facilities, a harmonious work atmosphere, and good social relationships between coworkers, can make work more productive and enjoyable. In addition, it has been proven that maintaining a balance between personal and work life is essential in reducing stress and increasing employee satisfaction. If educators can maintain this balance, they feel healthier and better prepared to face challenges in the workplace. Policies supporting these three components can positively impact achieving educational goals and increasing work motivation. Schools should create a supportive work environment, increase employee engagement through training and rewards, and create policies that support work-life balance.